Crisis Governance in Bangladesh: Bureaucracy, Inter-Departmental Coordination, and the COVID-19 Challenge - Md. Shahenur Islam; Mohammad Mahfuzur Rahman; Md. Iqramul Haque (Asian Studies, 2025)
The research is carried out to analyze the role of bureaucracy in COVID-19 governance in Bangladesh. Also, it explored the underlying issues of managing interdepartmental coordination during the pandemic. Secondary research data is collected from an interpretivist philosophical stance and analyzed in an inductive research approach. The qualitative research method is applied for in-depth analysis to provide a snapshot of the bureaucracy in COVID-19 governance and management of interdepartmental coordination in Bangladesh to fight the outbreak in the best regard. The paper found that the bureaucracy plays three major roles during the pandemic, such as implementation, administration, and regulation. The bureaucracy put the policy into practice by coordinating with the associated departments. Also, bureaucracy administered the situation by controlling, planning, and organizing available resources and opportunities. Hence, procrastination occurred to implement the policy, such as budgetary allocation for the emergency during the COVID-19 pandemic. In addition, the bureaucracy regulated during the pandemic due to the noncompliance of the people in terms of fines, judicial cases, and other minor punishments. The paper recommends a comprehensive law should be passed for situations like the COVID-19 pandemic to resolve legal issues. For proper administration, flexibility should be included instead of focusing on the red tape process. Further, the scope of the bureaucrat’s participation in the decision-making process should be increased.